2021
DOI: 10.1680/jmacr.19.00276
|View full text |Cite
|
Sign up to set email alerts
|

Chloride diffusion and time to corrosion initiation of reinforced concrete structures

Abstract: The diffusion mechanism for chloride ions in concrete with varying water/cement ratio (w/c) is studied by chloride ion spray testing. A new model of chloride diffusion coefficient, which varies with the ingress depth of chloride ion and w/c, is developed. A spatial time-dependent reliability model of time to corrosion initiation (TCI) for reinforced concrete (RC) structures is developed, considering spatial variability of geometric, material and environmental parameters. The test results show that the chloride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The authors found that this method provides additional and useful information for the probabilistic durability design and possible maintenance strategies at member level. (Peng et al, 2021) found that the probability of corrosion initiation considering spatial variability is 13-18% greater than that without consideration of spatial variability. This indicates that neglecting spatial variations in evaluating probability of corrosion initiation overestimates the structural reliability.…”
Section: Application Of Modelling Spatial Variability In Structural R...mentioning
confidence: 92%
“…The authors found that this method provides additional and useful information for the probabilistic durability design and possible maintenance strategies at member level. (Peng et al, 2021) found that the probability of corrosion initiation considering spatial variability is 13-18% greater than that without consideration of spatial variability. This indicates that neglecting spatial variations in evaluating probability of corrosion initiation overestimates the structural reliability.…”
Section: Application Of Modelling Spatial Variability In Structural R...mentioning
confidence: 92%
“…The chloride diffusion coefficient should also consider the temperature effect, which can be presented as [47]:…”
Section: Relationship Between the Diffusion Coefficient And Time Temp...mentioning
confidence: 99%